Uji Resistensi Bakteri Endofit dari Akar Eceng Gondok (Eichhornia crassipes) terhadap Linear Alkylbenzene Sulfonate - Arini Nurul Mahmudah; Agustina, Eva; Faizah, Hanik (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Linear Alkylbenzene Sulfonate (LAS) is an anionic surfactant with the potential to cause environmental pollution. One effective bioremediation strategy to mitigate this pollution is the use of endophytic bacteria. This study aims to evaluate the resistance ability of endophytic bacteria isolated from the roots of water hyacinth against LAS. The research was conducted as a laboratory-based experimental study using a Completely Randomized Design with five replications for each isolated endophytic bacterium. Bacterial resistance to LAS was tested in a liquid medium containing 10 ppm LAS and incubated for 14 days. The resistance level was determined based on the bacterial optical density (OD) measured using UV-VIS spectrophotometry. The results identified four endophytic bacterial isolates belonging to the genera Bacillus, Streptomyces, Micrococcus, and Neisseria, all of which exhibited resistance to LAS. The highest resistance level was observed in Streptomyces with an average OD value of 0.728 ± 0.11, while the lowest resistance was found in Bacillus with an average OD value of 0.361 ± 0.04.